Quantificação de endotoxinas e sua relação com sinais / sintomas e volumetria da lesão periapical e do canal radicular em dentes com infecção endodôntica primária - Cardoso, Flávia Goulart da Rosa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aims of the present study were: a) quantify endotoxins and bacterial CFU counts in primary endodontic infections before and after biomechanical preparation (BP) and after root canal medication (RCM); b) to correlate the levels of endotoxins and bacterial CFU counts with the volume of periapical bone destruction (VPBD) determined by Cone Beam Computed Tomography (CBCT) analysis as well as with the development of clinical signs and symptoms; c) to correlate the levels of endotoxins and bacterial CFU counts with the volume of the lumen of the canal (VLC); d) to correlate the size of periapical lesions determined by periapical radiographs images with the CBCT images. Thirty teeth with pulp necrosis and apical periodontitis were selected and submitted to CBCT analysis. After access to pulp cavity, a first root canal sampling was performed in order to determine the presence of root canal infection. Afterwards, BP was performed using 2.5% NaOCl followed by the placement of RCM according to the selection group: Calcium Hydroxide [Ca(OH)2] - Ca(OH)2 + Saline Solution (SSL); Ca(OH)2 + Ginger - Ca(OH)2 + 20% glycolic Ginger extract ; Ca(OH)2 + Chlorhexidine (CHX). A second collect were made after the BP and then the third after 14-days of RCM. Culture analysis was performed in order to determine antimicrobial activity. The levels of endotoxins were determined by the Limulus Ameboyte Lysate assay. The VPBD and the VLC were determined by CBCT-analysis and compared to periapical radiographs. Data were typed on a spreadsheet and statistical analyzed. At the baseline samples, CFU counts and endotoxins levels ranged from 0 - 8.16 CFU/mL and 1.75 -149 EU/mL, respectively. Both contents were reduced after BP and after RCM. Positive correlations were found between the levels of endotoxins and VPBD as well as with previous episode of pain. Thereby, a positive correlation was found between the bacterial...

Os objetivos do presente estudo foram: a) quantificar endotoxinas e carga microbiana nas infecções endodônticas primárias, antes e após o preparo biomecânico (PBM) e uso de diferentes medicações intracanais (MIC); b) relacionar níveis de endotoxinas e microrganismos cultiváveis com a volumetria da lesão periapical (VLP), através do uso de tomografias computadorizadas de feixe cônico (TCFC), verificando possíveis relações com sinais e sintomas clínicos; c) relacionar os mesmos níveis com a volumetria dos canais radiculares (VCR); d) Comparar medidas das lesões utilizando radiografias periapicais (RP) e tomografias computadorizadas de feixe cônico (TCFC). Foram selecionados para o estudo trinta dentes com necrose pulpar e lesão periapical que foram submetidos a TCFC. Após abertura coronária, foi realizada coleta inicial para verificação da presença de infecção nos canais radiculares. Após, procedeu-se o tratamento endodôntico utilizando solução de NaOCl 2,5% e divididos em 3 grupos de acordo com a MIC: Ca(OH)2 - hidróxido de cálcio P.A. + solução salina fisiológica; Ca(OH)2 + GEN - hidróxido de cálcio P.A. + extrato glicólico de gengibre 20% e Ca(OH)2 + CLX - hidróxido de cálcio P.A. + clorexidina gel 2%. Foram realizadas coletas do canal radicular após o PBM e após 14 dias de ação da MIC. Para todas as coletas foram realizados testes de atividade antimicrobiana por cultura microbiológica e análise da quantificação de endotoxinas pelo lisado de amebócitos de Limulus. Foi realizada a VLP e a VCR através da TCFC; e comparadas medidas de segmentação 2D das lesões periapicais das RP e das TCFC. Todos os dados foram analisados estatisticamente. Os resultados mostraram: a) presença de microrganismos na coleta inicial variando de 0 - 8,16 x 106 UFC/mL e níveis de endotoxinas de 1,75 - 149 EU/mL; havendo redução significante de seus níveis de ...
Keywords: Endodontia; Endotoxina; Tomografia Computadorizada de Feixe Cônico; Endodontics